Genome-wide association study revealed novel loci which aggravate asymptomatic hyperuricaemia into gout. Issue 10 (8th July 2019) - Kawamura, Yusuke; Nakaoka, Hirofumi; Nakayama, Akiyoshi; Okada, Yukinori; Yamamoto, Ken; Higashino, Toshihide; Sakiyama, Masayuki; Shimizu, Toru; Ooyama, Hiroshi; Ooyama, Keiko; Nagase, Mitsuo; Hidaka, Yuji; et al.
Abstract : Objective: The first ever genome-wide association study (GWAS) of clinically defined gout cases and asymptomatic hyperuricaemia (AHUA) controls was performed to identify novel gout loci that aggravate AHUA into gout. Methods: We carried out a GWAS of 945 clinically defined gout cases and 1003 AHUA controls followed by 2 replication studies. In total, 2860 gout cases and 3149 AHUA controls (all Japanese men) were analysed. We also compared the ORs for each locus in the present GWAS (gout vs AHUA) with those in the previous GWAS (gout vs normouricaemia). Results: This new approach enabled us to identify two novel gout loci (rs7927466 of CNTN5 and rs9952962 of MIR302F ) and one suggestive locus (rs12980365 of ZNF724 ) at the genome-wide significance level (p<5.0×10 – 8 ). The present study also identified the loci of ABCG2, ALDH2 and SLC2A9 . One of them, rs671 of ALDH2, was identified as a gout locus by GWAS for the first time. Comparing ORs for each locus in the present versus the previous GWAS revealed three 'gout vs AHUA GWAS'-specific loci ( CNTN5, MIR302F and ZNF724 ) to be clearly associated with mechanisms of gout development which distinctly differ from the known gout risk loci that basically elevate serum uric acid level. Conclusions: This meta-analysis is the first to reveal the loci associated with crystal-induced inflammation, the last step in gout development that aggravates AHUA into gout. Our findings should help to elucidate the molecular mechanisms of gout development and assist the prevention of gout attacks in high-risk AHUA individuals.